Peran dan Fungsi Keluarga dengan Anggota Keluarga Pasca Stroke di Desa Grogol, Puskesmas Cukir - Putri, Armelia Libriantari; Pawiono; Kurdi, Fahruddin (Jurnal Kesehatan Komunitas Indonesia, 2016)
Stroke not only affects the sufferer, but also affects the role and function in the family when the sufferer is being treated at home by his/her family. This study aims to determine how the role and function of the family with post-stroke family members at the Cukir Health Center really needs to be observed, so that it can be known how the role and function of post-stroke family members at home are. The design of this study is qualitative with a phenomenological approach. The research instrument comes from the researcher himself and the research subjects using purposive sampling. The data collection technique uses interview techniques. The data analysis technique uses the Moustakas analysis method. Data validity uses member check and triangulation. The results of the study showed that not all roles and functions in families with post-stroke family members changed. The role of the father, the role of the mother, economic function, biological function, and psychological function changed, while the role of the child, socialization function and educator function did not change after one of the family members had a post-stroke. It is hoped that further research with a larger number of participants and research locations will produce maximum results. It is recommended for families to maintain a sense of comfort at home and be more patient in dealing with patients during the healing process.